Integration of Wind Power for Sustainable Energy at Lagos State University of Science and Technology: A Feasibility Study - Akachukwu Oyim; Opeyemi Akerekan; Nwachukwu Ogbonna (Journal of Digital Food, Energy & Water Systems)
This study investigates the feasibility of integrating wind power generation at Lagos State University of Science and Technology, specifically within the Mechanical Engineering Department, to address persistent electricity supply challenges in Nigeria. The research focuses on the application of a five-bladed horizontal axis wind turbine (HAWT) and emphasizes the urgent need for sustainable energy solutions due to the depletion of conventional sources and the environmental impact of fossil-fuel-powered generators. The methodology involves mathematical modelling to analyze wind shear exponent, Weibull distribution, maximum power available, and capacity factor. Utilizing the FZ-3000 five-bladed HAWT, data is collected using a wireless wind anemometer.